Strategi Pendidikan Agama Islam pada Pembelajaran Akidah "Pencegahan dan Penanggulangan Penyebaran Aliran Sesat" - Mia Fitriah Elkarimah (SAP (Susunan Artikel Pendidikan), 2017)
This research aims to describe the strategy of Islamic Education (PAI) on learning of aqidah in formal educational institutions, especially in public school in an effort to prevent and overcome a heresy in SMK Teratai Putih Global 4 Bekasi. The problem of learning aqidah in Islamic education in public school is the lack of time which is only 2 hours a week. This qualitative research uses a case study technique, in which the data are acquired through an interview, document analysis, participatory observation and triangulation techniques. In this research, the researcher uses qualitative data related to issues to be discussed, namely the strategy of preventing and overcoming a heresy. The result of the research shows that in general, strategy of Islamic education on aqidah learning includes: 1) Incorporating aqidah materials on heresy prevention through Islamic Education subject in initial assistance (introduction) or before teaching the materials. The substance is providing information or understanding related to a heretical movement (haraqah), then explaining its criteria, recruitment strategies, dangers and tips to avoid its persuasion. 2), learning aqidah routinely for 5 minutes after performing dzuhur prayer together, 3) providing aqidah mentoring to student’s Islamic organization (rohis).